1976
DOI: 10.1037/0021-843x.85.4.341
|View full text |Cite
|
Sign up to set email alerts
|

A 10-year perspective of motherless-mother monkey behavior.

Abstract: Previous studies have reported that the maternal behavior of rhesus monkey females who themselves were reared without mothers ("motherless mothers") is generally inadequate and often abusive. The present study examined the maternal competency of SO such subjects with respect to the variables of rearing environment, age at first social contact, sex of offspring, age at first delivery, parity, and duration of exposure to previous offspring. The results suggested that physical contact with conspecifics, either wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
116
1
1

Year Published

1981
1981
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 181 publications
(124 citation statements)
references
References 10 publications
6
116
1
1
Order By: Relevance
“…Most infant play occurred in the second and in the third month of infant life whereas most abuse was concentrated in the first weeks, thus suggesting that the difference in play may have been a consequence of early abuse. Other studies of infant abuse in individually housed and group-living macaques have shown that abuse increases infant clinging and delays the acquisition of infant independence from their mothers, at least temporarily (Maestripieri, 1998;Ruppenthal et al, 1976). More studies are needed to accurately assess the long-term consequences of early abuse on social and psychological development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most infant play occurred in the second and in the third month of infant life whereas most abuse was concentrated in the first weeks, thus suggesting that the difference in play may have been a consequence of early abuse. Other studies of infant abuse in individually housed and group-living macaques have shown that abuse increases infant clinging and delays the acquisition of infant independence from their mothers, at least temporarily (Maestripieri, 1998;Ruppenthal et al, 1976). More studies are needed to accurately assess the long-term consequences of early abuse on social and psychological development.…”
Section: Discussionmentioning
confidence: 99%
“…Infant abuse has been observed in both mothers reared and housed in conditions of social deprivation (Reite & Caine, 1983;Ruppenthal, Arling, Harlow, Sackett, & Suomi, 1976) and mothers born and reared in social groups (hereafter group-living), in captivity and in the wild (Hiraiwa, 1981;Maestripieri, 1994aMaestripieri, , 1998Troisi, D'Amato, Fuccillo, & Scucchi, 1982). Whereas infant abuse displayed by socially deprived monkeys is only one example of a host of abnormal social behaviors, group-living abusive mothers are otherwise normal individuals who possess and display a full range of competent social behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Nulliparous rhesus monkeys generally avoid sncklihgs. Ruppenthal et al (1976) noted that indifferent mothers were older at first delivery than abusive mothers and suggested that full maturity could have ameliorated abusive behavior. They also found that primiparous mothers were superior at the age of 8 years and suggested that full maturation of the hormonal system could be achieved then.…”
Section: Discussionmentioning
confidence: 99%
“…Of course another prerequisite for learning is that the primipara which stays with her infant performs true maternal behavior. Among solitarily-reared rhesus females (Ruppenthal et al, 1976), indifferent mothers had the opportunity to interact with their firstborn infants for a few days during some hours a day. Although paying no attention to their firstborn, they often accepted their next infants.…”
Section: Discussionmentioning
confidence: 99%
“…For example, regarding the role of experience--or lack thereof--as a determinant of inadequate maternal behavior, it must be noted that the increase in the proportion of adequate maternal care with successive infants was solely due to a reduction in indifference and neglect and not in abuse, which remained constant with successive offspring (Ruppenthal et al, 1976). Similarly, peer rearing was associated with a lower occurrence of infant neglect but not of abuse (Suomi, 1978).…”
Section: Interpretation Of the Findingsmentioning
confidence: 99%